2020
DOI: 10.20517/2574-1225.2020.70
|View full text |Cite
|
Sign up to set email alerts
|

Robotic surgery of gallbladder cancer

Abstract: Aim: The aim of this study was to describe our technique for the surgical treatment of clinically suspected or incidentally diagnosed gallbladder cancer (GBC) and to report the outcomes of our experience. Methods: This is a retrospective observational study including consecutive patients operated by a robotic approach for the surgical treatment of clinically suspected or incidentally diagnosed GBC (with the intent of radical reresection after index cholecystectomy) performed between January 2017 and December 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 31 publications
(35 reference statements)
0
3
0
Order By: Relevance
“…This evidence together with the appropriateness of loco-regional lymphadenectomy and the reduced intraoperative blood loss reported in the majority of the analyzed studies, allow us to consider the laparoscopic approach non inferior to the open one in terms of operative outcomes. Therefore, is not surprising that the minimally invasive approach has been recently extended to the surgical treatment of hilar type cholangiocarcinoma[ 36 ] and gallbladder cancer[ 37 , 38 ]. These encouraging pivotal experiences seem to demonstrate the feasibility of minimally invasive surgery in a setting often requiring the completion of a major hepatic resection in association with loco-regional lymphadenectomy and the challenge of biliary reconstructions.…”
Section: Discussionmentioning
confidence: 99%
“…This evidence together with the appropriateness of loco-regional lymphadenectomy and the reduced intraoperative blood loss reported in the majority of the analyzed studies, allow us to consider the laparoscopic approach non inferior to the open one in terms of operative outcomes. Therefore, is not surprising that the minimally invasive approach has been recently extended to the surgical treatment of hilar type cholangiocarcinoma[ 36 ] and gallbladder cancer[ 37 , 38 ]. These encouraging pivotal experiences seem to demonstrate the feasibility of minimally invasive surgery in a setting often requiring the completion of a major hepatic resection in association with loco-regional lymphadenectomy and the challenge of biliary reconstructions.…”
Section: Discussionmentioning
confidence: 99%
“…The advent of robotic surgery is certainly another milestone in the evolution of minimally invasive surgery, even if the benefits are still a matter of debate for many subspecialties. With regard to GBC, several reports have been published [ 76 ]. Goel et al showed their results on 27 patients undergoing robotic surgery for GBC, with lower intraoperative bleedings and length of hospital stay when compared with an open approach, confirming its safety and feasibility [ 77 ].…”
Section: Clinical Management According To the Depth Of Invasionmentioning
confidence: 99%
“…While a randomized trial for a rare pathology is not feasible, larger cohort studies could still be conducted[ 82 , 83 ]. At present, the technical approach for the robotic surgery of GBC has been described in the literature, such as that of Belli et al [ 84 ]. Similar to the laparoscopic approach, the patient is positioned in reverse-Trendelenburg, with five ports being used which include the 3 ports for robotic instrumentation, 1 for the camera and 1 Laparoscopic port for an assistant surgeon[ 84 ].…”
Section: Newer Approaches To Managementmentioning
confidence: 99%